Land Provision for Decent and Affordable Housing for Low-Income Community in Salatiga City - S Sunarti; Nany Yuliastuti; I Indriastjario (Geoplanning: Journal of Geomatics and Planning, 2019)
The needs land for urban housing construction was increasingly difficult andmore pricey, so for low-income communities for able owned a house was not easy.Limited of land in an urban area, especially in small cities such as Salatiga, its land wasnot all can be used in housing constructions. This condition needed an interventionfrom the local government to facilitate their needs for housing could be fulfilled. Basedon the problems, the goals of this research studied a providing of land for decent andaffordable housing for low-income communities in Salatiga. The method used was amixed method with a sequential explanation strategy, that is by overlaying secondarydata on the land potential map from various sources that can be used for decenthousing with primary data, such as interview and document review with localgovernment to reduce of housing cost. The results of the study figure out that housingused a land owned by the village government can be affordable for low-incomecommunities with price less expensive below the standard set by the government.